In the name of Honor : a novel - Patterson, Richard North (New York : Henry Holt and Co., 2010)
An Iraq veteran shoots his commanding officer, who was married to a family friend.
Keywords: Iraq War, 2003-2011 -- Veterans -- Fiction; War -- Psychological aspects -- Fiction; Families of military personnel -- Fiction; Suspense fiction